2021
DOI: 10.1186/s12992-021-00764-7
|View full text |Cite
|
Sign up to set email alerts
|

Who influences nutrition policy space using international trade and investment agreements? A global stakeholder analysis

Abstract: Background Regulation of food environments is needed to address the global challenge of poor nutrition, yet policy inertia has been a problem. A common argument against regulation is potential conflict with binding commitments under international trade and investment agreements (TIAs). This study aimed to identify which actors and institutions, in different contexts, influence how TIAs are used to constrain policy space for improving food environments, and to describe their core beliefs, intere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 55 publications
0
11
0
Order By: Relevance
“…Within the social rituals, processed foods containing large amounts of sugar were embedded in a variety of recurring habits such as sugared coffee, sugared cakes in the afternoon, and sugary foods on birthdays, Easter, Halloween, and Christmas, as only some examples [ 81 , 82 ]. Within the capitalized system, food industries influence “consumers” through advertisements and political lobbyism to continue a Western type of diet [ 83 , 84 , 85 ]. Even in the field of dental research, the sugar industry influenced the research agenda of the U.S. National Institute of Dental Research (NIDR) to avoid research dealing with sugar reduction strategies [ 86 ].…”
Section: Neolithization and Industrial Revolution Cultural Evolution ...mentioning
confidence: 99%
“…Within the social rituals, processed foods containing large amounts of sugar were embedded in a variety of recurring habits such as sugared coffee, sugared cakes in the afternoon, and sugary foods on birthdays, Easter, Halloween, and Christmas, as only some examples [ 81 , 82 ]. Within the capitalized system, food industries influence “consumers” through advertisements and political lobbyism to continue a Western type of diet [ 83 , 84 , 85 ]. Even in the field of dental research, the sugar industry influenced the research agenda of the U.S. National Institute of Dental Research (NIDR) to avoid research dealing with sugar reduction strategies [ 86 ].…”
Section: Neolithization and Industrial Revolution Cultural Evolution ...mentioning
confidence: 99%
“…The lead author systematically coded each of the interviews and literature review sources according to themes in line with the ACF, in NVivo . The methods used and findings of this phase of the study are described in detail elsewhere (Garton et al, 2021c).…”
Section: Policy Scenario Analysis Through Vignette Interviewsmentioning
confidence: 99%
“…Our stakeholder analysis (combining the realist review and interview data), identified five strategies used by industry and economic growth coalitions to constrict policy space through TIAs: (1) influencing government trade ministries' internal vetting of regulatory proposals; (2) convincing and supporting host governments to raise specific trade concerns and trade disputes, or raising own disputes in ISDS; (3) influencing TIA negotiations; (4) participation in Codex standards-setting; and (5) using transparency and consultation rules to influence food environment policymaking processes (Garton et al, 2021c).…”
Section: Actors Institutions and Coalitionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Newer interpretive summary indicator FoPL systems are possibly more effective at influencing identification and choice of healthy foods by consumers than non‐interpretative systems, such as the GDA (Croker et al, 2020). However, the food industry prefers the GDA and is lobbying and leveraging networks to influence country FoPL schemes in numerous countries (Garton et al, 2021; Mialon et al, 2021; Pedroza‐Tobias et al, 2021). Pioneering FoPL countries, like Thailand and Chile, have taken different paths over the last decade to implement their current schemes, offering examples of new elements to consider, such as the possible value of regional momentum and cross‐country solidarity in successfully developing effective national FoPL schemes (Boza et al, 2020; Pérez‐Escamilla et al, 2021; World Cancer Research Fund International, 2019).…”
Section: Introductionmentioning
confidence: 99%